Bestimmung des Sprachstands in einer Herkunftssprache: Ein Vergleich verschiedener Testverfahren am Beispiel des Polnischen als Herkunftssprache in Deutschland. Determining proficiency in a heritage language: A comparison of different testing methods based on Polish as a heritage language in Germany - Brehmer, Bernhard (Glottodidactica, 2016)
The paper discusses several methods of evaluating heritage speakers’ abilities in their heritage language. Speech rate in spontaneous text production, lexical knowledge and grammatical proficiency in the heritage language have been found to correlate strongly with one another. Therefore, they are recommended in the literature as quick and reliable diagnostics for establishing the general degree of heritage language maintenance among heritage speakers. Based on data from 20 heritage speakers of Polish in Germany, the current paper shows that lexical and grammatical proficiency are indeed strongly correlated, but speech rate did not turn out to be an indicator for heritage language proficiency in the examined population.